Technological interventions enriching tropical fruit growers - Dinesh, M R; Sankaram, K M (Indian Horticulture, 2019)
Diversification in horticultural crops is becoming attractive for many poor farmers around the world. Among horticultural crops, fruit trees provide not only fruits but also have varied uses, viz. for medicinal products, fodder, as well as fuel wood and timber. In addition to economic benefits, fruit trees provide enormously to ecosystem services. The Government of India has come out with a slogan â€œDoubling farmersâ€, income by 2022" by focusing not only on increasing crop yields but also on reducing the cost of cultivation to increase the net income of farmers. Some varieties and technologies, which can increase our farmersâ€™ income manifolds are discussed.